WORKSHOP E-MODUL INTERAKTIF DENGAN CANVA UNTUK PEMBELAJARAN PADA MASA PANDEMI COVID-19 - Ni Wayan Switrayni; I Gede Adhitya Wisnu Wardhana; Irwansyah Irwansyah; Qurratul Aini; Salwa Salwa (Jurnal Abdi Insani, 2022)
The COVID-19 pandemic has affected various aspects of life in Indonesia, one of which is the education sector. For example, during the COVID-19 pandemic, most junior high school teachers, especially at the Islamic Junior High School Pondok Pesantren At-Tamimy, only used textbooks as teaching materials which of course were less effective and interactive. Therefore, this Community Service (PkM) activity aims to introduce teachers at the Islamic Junior High School Pondok Pesantren At-Tamimy with interactive e-modules for online learning using Canva. The results of this activity indicate that the implementation of this Community Service Activity has been running quite well and smoothly. Through this workshop, the teachers of the Islamic Junior High School Pondok Pesantren At-Tamimy were given tutorials on making interactive e-modules which can actually not only be used in the online learning process during the COVID-19 pandemic, but can also be used for more efficient, effective offline learning. and fun because teachers can be creative in making e-module designs as attractive as possible for students. Based on the explanation of the results of the implementation of this activity, it can be concluded that the team has carried out the workshop well, smoothly, and fun because teachers can be creative in making e-module designs that are as attractive as possible.